2007
DOI: 10.1093/jn/137.4.945
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Linoleic Acid with Constant α-Linolenic Acid in Dietary Fats Increases (n-3) Eicosapentaenoic Acid in Plasma Phospholipids in Healthy Men1

Abstract: High linoleic acid (LA) intakes have been suggested to reduce alpha-linolenic acid [ALA, 18:3(n-3)] metabolism to eicosapentaenoic acid [EPA, 20:5(n-3)] and docosahexaenoic acid [DHA, 22:6(n-3)], and favor high arachidonic acid [ARA, 20:4(n-6)]. We used a randomized cross-over study with men (n = 22) to compare the effect of replacing vegetable oils high in LA with oils low in LA in foods, while maintaining constant ALA, for 4 wk each, on plasma (n-3) fatty acids. Nonvegetable sources of fat, except fish and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(145 citation statements)
references
References 52 publications
12
127
1
5
Order By: Relevance
“…Moreover, the plasma levels of long-chain n-3 PUFA were negatively correlated with that of linoleic acid, which indicates that the conversion of a-linolenic into long-chain derivatives can be inhibited by high linoleic acid intakes. This has been confirmed in recent intervention studies, in which the intakes of high levels of linoleic acid (7-10% of calories compared to 3-4%) were found to lower the conversion of a-linolenic into EPA, in subjects maintained on diets devoid of fish and seafood (Goyens et al, 2006;Liou et al, 2007). In our study, where the intake of long-chain n-3 PUFA was fairly high (95% of the population consumed more than 0.06% of energy or 100 mg/day) (Astorg et al, 2004), the levels of linoleic acid and a-linolenic intakes were not found to influence the long-chain n-3 PUFA plasma levels, since the endogenous biosynthesis of these PUFA from a-linolenic was likely to be negligible compared to their direct dietary supply.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, the plasma levels of long-chain n-3 PUFA were negatively correlated with that of linoleic acid, which indicates that the conversion of a-linolenic into long-chain derivatives can be inhibited by high linoleic acid intakes. This has been confirmed in recent intervention studies, in which the intakes of high levels of linoleic acid (7-10% of calories compared to 3-4%) were found to lower the conversion of a-linolenic into EPA, in subjects maintained on diets devoid of fish and seafood (Goyens et al, 2006;Liou et al, 2007). In our study, where the intake of long-chain n-3 PUFA was fairly high (95% of the population consumed more than 0.06% of energy or 100 mg/day) (Astorg et al, 2004), the levels of linoleic acid and a-linolenic intakes were not found to influence the long-chain n-3 PUFA plasma levels, since the endogenous biosynthesis of these PUFA from a-linolenic was likely to be negligible compared to their direct dietary supply.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, animals fed ground cottonseed exhibited greater n-6 fatty acid concentrations in muscle, and n-6/n-3 ratio in both tissues, compared with those fed ground soybean. The relationship between these fatty acids is important because high intake of n-6 fatty acids can inhibit conversion of α-linolenic to EPA (Liou et al, 2007). Oliveira et al (2011) also observed a greater n-6/n-3 ratio in the muscle and subcutaneous fat from animals fed cottonseed diets compared with animals fed soybean or linseed diets.…”
Section: Resultsmentioning
confidence: 96%
“…AA is the substrate for the production of a wide variety of pro-inflammatory eicosanoids (Harris et al, 2009). Although the metabolites of ALA possess anti-inflammatory actions, higher n-6 PUFA intakes can inhibit the conversion of ALA to EPA (Das, 2006;Liou et al, 2007). De Vizia et al (2003) reported an increase in EPA and DHA in erythrocyte membrane phospholipids after supplementation with fish oil as a source of EPA and DHA in patients with CF.…”
Section: Discussionmentioning
confidence: 99%